Adsorpsi Logam Cu dengan Graphene Oksida - Raihan Nurfauziah; Zulfa Rahmah Fadillah; Sinta Setyaningrum; Eko Andrijanto (Jurnal Kimia Fullerene, 2021)
The development of industry around the river causes an increase in pollutants flowing in the river. One type of industrial pollutant is heavy metals. Heavy metals are toxic and toxic, so the presence of heavy metals in the aquatic environment can damage aquatic ecosystems. One of the ways to remove heavy metals is by using the isotherm adsorption method. Namely the process where the absorption of heavy metals on the surface of solids, namely the adsorbent. The adsorbent used is a graphene oxide sand composite which is made from carbon and has a high potential to remove heavy metal pollutants. The experiment was carried out by mixing the adsorbent with a solution of Cu2+ metal ions and adsorption was carried out using several parameters, namely variations in contact time and adsorption pH and measurements were made using a visible spectrophotometer. Optimum absorption occurs at the 25th minute contact time with an efficiency of 96.2% and at an adsorption pH of 8 with an efficiency of 99.4%. So it can be concluded that graphene oxide sand composite can be used to remove heavy metal pollutants.